2022
DOI: 10.1007/s13132-022-00924-z
|View full text |Cite
|
Sign up to set email alerts
|

Legal Technology: Assessment of the Legal Tech Industry’s Potential

Abstract: The use of information and communication technologies (ICT) in the sector of legal services has resulted in the emergence of a new category of services known as legal technology (legal tech). This article aims at defining the current state of research concerning the matter, confirming its interdisciplinary nature and examining the level of its popularity. The strategy assumed for the article has influenced the order and sequence of the topics covered starting from an introduction to legal technology together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Second, we set out to identify potentially relevant recent "industry surveys" to seek concrete evidence on this topic (Mania 2023). In the absence of a searchable repository for these industry surveys, we first searched the academic literature for any systematic reviews of survey evidence and found one book chapter, albeit on a slightly different topic (Weinstein 2022).…”
Section: Methodological Appendixmentioning
confidence: 99%
“…Second, we set out to identify potentially relevant recent "industry surveys" to seek concrete evidence on this topic (Mania 2023). In the absence of a searchable repository for these industry surveys, we first searched the academic literature for any systematic reviews of survey evidence and found one book chapter, albeit on a slightly different topic (Weinstein 2022).…”
Section: Methodological Appendixmentioning
confidence: 99%
“…The thematic literature review approach is an analytical method that focuses on examining a specific theme or topic within relevant literature (Carr, 2002). In the research context, this approach involves the systematic identification, collection, and synthesis of literature related to the research theme or topic (Mania, 2023). The first step in this approach is to determine the theme or topic to be explored, followed by devising a strategy for literature search that is pertinent to that theme.…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis can be used to identify the most influential authors, institutions, and publications in a field as well as to track the evolution of research topics over time. It can also be used to identify research gaps and guide future research directions (Ben-Daya et al, 2017;Kutera, 2022;Pahlevi, 2022;Mania, 2022;Singla, 2023). The methodology typically involves using specialized software tools, such as VOSviewer, to analyze and visualize bibliographic data.…”
Section: Methodsmentioning
confidence: 99%